(untitled) (Medical Forum Monthly, 2021)
Objective: To determine the frequency of non-ST elevation myocardial infarction (NSTEMI) in patients presenting at cardiology emergency with acute coronary syndrome and having normal ECG. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the Emergency Department of Cardiology, Chaudhry Pervaiz Elahi Institute of Cardiology (CPEIC), Multan, from Nov, 2019 to May, 2020. Materials and Methods: A total number of 203 patients presenting with Acute Coronary Syndrome aged 30-80 years. Data, including the patient's age, gender, BMI, family history, diabetes, smoking, and hypertension, was collected. Patients having trop-T >0.4 ng/ml were labelled as having NSTEMI. All patients with NSTEMI was undergone standard 12- lead ECG tracing. ECG findings (normal/ ST-depression, T-wave inversion) was noted. Results: Mean age was 53.34±11.51 years included in this study. The BMI was 25.11±3.26 kg/m2. There were 137 (67.49%) males and 66 (32.51%) female patients. There were 75 (36.95%) diagnosed with diabetes. Hypertension was found in 107 (52.71%). Family history of was found in 37 (18.23%). 70 (34.48%) out of 203 patients were smokers. NSTEMI with normal ECG was diagnosed in 19 (9.36%) patients. Conclusion: There is value to completely normal ECG findings acquired in suspected patients of NSTEMI in the emergency department. In the present study, 9.36% of patients who had the suspicion of NSTEMI was found to have normal ECG and diagnosis in these patients were made on clinical symptoms and trop-T values.